Rosemary's baby - Polanski, Roman; Castle, William; Farrow, Mia, 1945-; Cassavetes, John, 1929-1989.; Gordon, Ruth, 1896-1985.; Blackmer, Sidney, 1895-1973.; Evans, Maurice, 1901-1989.; Bellamy, Ralph, 1904-1991.; Levin, Ira.; Paramount Pictures Corporation (Hollywood, Calif : Paramount Pictures, 2000)
After unwittingly becoming friendly with a coven of witches and warlocks, a young wife is impregnated by the Devil.
Widescreen format.
Based on the novel by Ira Levin.
Originally released as a motion picture in 1968.
Special features include: Interactive menus ; scene selection ; retrospective interviews with Roman Polanski, Robert Evans and Richard Sylbert ; "making of" featurette.
Screenplay, Roman Polanski ; producer, William Castle ; director, Roman Polanski.
Mia Farrow, John Cassavetes, Ruth Gordon, Sidney Blackmer, Maurice Evans, Ralph Bellamy.
Keywords: Levin, Ira -- Film and video adaptations; Demoniac possession -- Drama; Satanism -- Drama; Pregnancy -- Drama; Childbirth -- Drama; Young families -- United States -- Drama; Feature films; Horror films; Video recordings for the hearing impaired